Modified ZIF-8 mixed matrix membrane for CO2/CH4 separation - Nordin, N.A.H.M. (American Institute of Physics Inc., 2017)
Tunability of metal-organic frameworks (MOFs) properties enables them to be tailored for specific applications. In this study, zeolitic imidazole framework 8 (ZIF-8), sub-class of MOF, underwent pre-synthesis and post-synthesis modifications. The pre-synthesis modification using GO (ZIF-8/GO) shows slight decrease in textural properties, while the post-synthesis modification using amine solution (ZIF-8/NH2) resulted in superior BET surface area and pore volume. Mixed matrix membranes (MMMs) derived from polysulfone (PSf) and the modified ZIF-8s were then prepared via dry/wet phase inversion. The polymer chain flexibility of the resulted MMMs shows rigidification, where ZIF-8/NH2 as filler resulting higher rigidification compared to ZIF-8/GO. The MMMs were further subjected to pure CO2 and CH4 gas permeation experiments. The PSf/ZIF-8/NH2 shows superior CO2/CH4 selectivity (88 increased) while sacrificing CO2 permeance due to combination of severe polymer chain rigidification and the presence of CO2-philic group, amine. Whereas, the PSf/ZIF-8/GO possess 64 increase in CO2 permeance without notable changes in CO2/CH4 selectivity. © 2017 Author(s).